KAJIAN PARAMETER GENETIK KARAKTER KUANTITATIF TANAMAN JAGUNG (Zea mays L.) DI LAHAN KERING - Juliati, Fasia; Sudika, I Wayan; Sutresna, I Wayan (AGROTEKSOS; Vol 33 No 1 (2023): Jurnal Agroteksos April 2023DO - 10.29303/agroteksos.v33i1.786, 2023)
The narrow-sense heritability and expected selection response are very important to be recognized in the F2 population of maize to determine the character to be selected. This study aim ed to estimate the narrow -sense heritability and the expected selection response of quantitative characters in the F2 population. The experimental method used in this study was field experiments on dry land using pumping wells for irrigation. This was conducted from April to October 2022 in Amor-Amor Hamlet, Gumantar village, North Lombok district. The experiment was carried out in two growing seasons; namely : the first growing season was to establish kinship with NC1 and the second season was to test the results of crosses by used a Randomized Block Design (RBD). The number of treatments was 105; derived from 35 male parents . Each treatment was rep licated 2 times, so there were 210 experimental units. Data were analyzed using analysis of variance (ANOVA); and then calculation of narrow sense heritability and response selection expectations was conducted. The results showed that the narrow sense heritability of all the quantitative characters observed was low , while t he selection response of the biomass weight per plant was high; Plant height , leaf angle , and dry cob weight per plant were moderate and other characters were low. Fresh biomass weight per plant can be used as a selection criterion for improving the stay-green character. Yield can be improved through enhancing dry cob weight per plant.   Keywords: corn; heritability; response of expected selection and dry land.